Cyclometalated iridium(III) complexes combined with fluconazole: antifungal activity against resistant C. albicans - Lu, Jun-Jian; Xu, Zhi-Chang; Zhu, Hou; Zhu, Lin-Yuan; Ma, Xiu-Rong; Wang, Rui-Rui; Li, Rong-Tao; Ye, Rui-Rong (Frontiers in Cellular and Infection Microbiology, 2023)
Candida albicans (C. albicans) is a ubiquitous clinical fungal pathogen. In recent years, combination therapy, a potential treatment method to overcome C. albicans resistance, has gained traction. In this study, we synthesized a series of cyclometalated iridium(III) complexes with the formula [Ir(C-N)2(tpphz)](PF6) (C-N = 2-phenylpyridine (ppy, in Ir1), 2-(2-thienyl)pyridine (thpy, in Ir2), 2-(2,4difluorophenyl) pyridine (dfppy, in Ir3), tpphz = tetrapyrido[3,2-a:2',3'-c:3'',2''-h:2''',3'''-j]phenazine) and polypyridyl ruthenium(II) complexes with the formula [Ru(N-N)2(tpphz)](PF6)2 (N-N = 2,2'bipyridine (bpy, in Ru1), 1,10-phenanthroline (phen, in Ru2), 4,7-diphenyl-1,10-phenanthroline (DIP, in Ru3)), and investigated their antifungal activities against drug-resistant C. albicans and their combination with fluconazole (FLC). Of which, the combination of the lead iridium(III) complex Ir2 and FLC showed strong antifungal activity against drug-resistant C. albicans. Mechanism studies have shown that they can inhibit the formation of hyphae and biofilm, damage mitochondrial function and accumulate intracellular ROS. Therefore, iridium(III) complexes combined with FLC can be used as a promising treatment to exert anti-drug-resistant C. albicans activity, in order to improve the treatment efficiency of fungal infection.